A Novel Target Detection and Identifying Approach Using Polarimetric Radar Cross-Section and Matrix Correlation Coefficient - Phruksahiran, Narathep (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2024)
This paper presents a novel target detection and identifying approach using polarimetric radar cross-section and matrix correlation coefficient. We have adopted a polarimetric radar cross-section matrix correlation strategy (PRMC) algorithm using a matrix correlation approach based on the polarimetric radar cross-section. It is projected as an inverse scattering problem under the electromagnetic scattering model using polarimetric Physical Optics approximation. The experimental measurements using canonical targets carried out under semicontrolled conditions verify the performance of the developed procedures. Finally, the identification strategies' effectiveness is demonstrated in free-space conditions and a scene with a brick and autoclaved aerated concrete wall.